A haunting in Venice [videorecording (Blu-Ray)] - Branagh, Kenneth; Green, Michael (Screenwriter); Allen, Kyle, 1994-; Cottin, Camille; Dornan, Jamie, 1982-; Fey, Tina, 1970-; Hill, Jude; Khan, Ali, 2001-; Laird, Emma; Reilly, Kelly; Scamarcio, Riccardo, 1979-; Yeoh, Michelle, 1962-; et al. (20th Century Studios, 2023)
Now retired and living in self-imposed exile in the world's most glamorous city, Poirot reluctantly attends a sǎnce at a decaying, haunted palazzo. When one of the guests is murdered, the detective is thrust into a sinister world of shadows and secrets.